Development of a novel biofeedback system for the sprint start - Cortes Gutierrez, J.; Walton, S. P.; Bezodis, N. E. (International Journal of Sports Science & Coaching, 2023)
This study developed and evaluated a novel concurrent biofeedback system for the sprint start. Previous studies have investigated sprint start biofeedback applications, but these have either not considered important kinematics, coaching implications or key motor learning principles. The biofeedback system was developed to convey rear knee angle information, obtained from 3D motion capture to novice participants as changes in the colour of an LED start line when they were in the "set" position. Based on initial user feedback, the system indicated whether the participants` rear knee angles were within ± 2° of 130° (green) or not (red). A two-group experimental study was then employed to explore the acute responses of novices to the use of the biofeedback system during the sprint start. When exposed to biofeedback, the experimental group (EXP, n = 10) exhibited less deviation (4.0 ± 2.4°) from the target rear knee angle than they did in either a pre-test (11.9 ± 6.9°) or post-test (10.4 ± 4.4°) condition without biofeedback. The control group (CON, n = 10) with no biofeedback exhibited greater deviation from the target rear knee angle than the EXP group in all three condition blocks (pre-test = 21.8 ± 15.1°, no intervention = 15.6 ± 7.3°, post-test = 14.3 ± 6.5°) but the group × condition interaction effect was not significant (P = 0.210). The novel biofeedback system can be used to manipulate selected "set" position kinematics and has the potential to be incorporated with different input systems (e.g. inertial measurement units (IMUs)) or in longitudinal designs.